(untitled) (Research, Society and Development, 2020)
The aim of this work was to obtain Brazil-soluble Brazil nut extract on a pilot scale, to determine the physical-chemical, microbiological, sensory and rheological characteristics of the products obtained and to determine the microbiological, physical-chemical and physical stability of the extract in presence and absence light and preservatives. This is a quantitative study, carried out in the laboratory. Extracts were characterized in terms of physicochemical (proximate composition, mineral profile, pH, titratable acidity, color), rheological (apparent viscosity, flow index, consistency coefficient), microbiological (yeast and molds, Salmonella sp., coliforms at 35ºC and at 45ºC and coagulase positive Staphylococcus), and sensory (odor, color, taste, global impression, buying intention) parameters. Furthermore, the effect of the addition of preservatives (500 mg/L citric acid, 0.15% w:v sodium benzoate and 0.1% w:v potassium sorbate) and of the exposure to light on the physicochemical (pH, titratable acidity), physical (color variation) and microbiological stabilities throughout storage were assessed. The extracts had high energy content, due to its high protein and fat contents, besides being a valuable source of selenium. The extracts were characterized as non-Newtonian pseudoplastic fluids, and were well accepted in sensory analysis, with up to 60% of the consumers indicating willingness to buy the product. The presence of preservatives at least doubled the shelf-life of the products, from 9 to up to 21 days. The incidence of light had no effect in the stability of the extracts.